2008
DOI: 10.1002/chem.200701494
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Photochemical [2+2] Cycloaddition in a Hydrogen‐Bonded Metal Complex Containing Several Parallel and Crisscross CC bonds

Abstract: One-dimensional hydrogen-bonded complex [Zn(bpe)(2)(H(2)O)(4)](NO(3))(2).8/3 H(2)O.2/3 bpe (1, bpe=4,4'-bipyridylethylene) containing coordination complex cations [Zn(bpe)(2)(H(2)O)(4)](2+) with parallel and crisscross double bonds undergoes photochemical [2+2] cycloaddition in the solid state and produces tetrakis(4-pyridyl)cyclobutane (tpcb) in up to 100 % yield with rctt-tpcb (2a) as major and rtct-tpcb (2b) as minor product. The bpe ligands with crisscross conformation of C=C bonds appear to undergo pedal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 129 publications
2
63
0
Order By: Relevance
“…Powder X-ray diffraction confirmed that the samples were phase pure and consisted mainly of the above reaction products (see supporting information). Single-crystal XRD confirmed the validity of our proposal about possible Zn (Table S3) and have the same underlying net; however, the networks of (7) and (9) (Peedikakkal & Vittal, 2008), it readily undergoes the [2 + 2] cycloaddition 0D!1D photoreaction to give a coordination polymer (see x2.4 for details).…”
Section: Crystallographysupporting
confidence: 80%
See 2 more Smart Citations
“…Powder X-ray diffraction confirmed that the samples were phase pure and consisted mainly of the above reaction products (see supporting information). Single-crystal XRD confirmed the validity of our proposal about possible Zn (Table S3) and have the same underlying net; however, the networks of (7) and (9) (Peedikakkal & Vittal, 2008), it readily undergoes the [2 + 2] cycloaddition 0D!1D photoreaction to give a coordination polymer (see x2.4 for details).…”
Section: Crystallographysupporting
confidence: 80%
“…We consider the insufficient investigation of photoinitiated reactions a result of the factors that govern the mutual disposition of reactive fragments, which are not well understood. With regards to metal complexes, mainly hydrogen bonds (Peedikakkal & Vittal, 2008) and metallophilic interactions (Georgiev et al, 2010;Chu et al, 2005;Schmidbaur & Schier, 2012) were used to carry out 0D!1D transformations, or in some cases, planar chelate (Papaefstathiou et al, 2004(Papaefstathiou et al, , 2005 and bridging (Mir et al, 2010;Sato et al, 2012;Nagarathinam & Vittal, 2006;Chanthapally et al, 2013;Toh et al, 2005) carboxylate anions were applied to fix the photo-sensitive species in reactive positions for intramolecular 1D!1D or 2D!2D reactions. For example, 1D coordination polymers with ladder-type structures are characterized by close and parallel orientation of the double bonds in photoreactive spacer ligands (depicted in black in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex Containing Several Parallel and Crisscross C═C Bonds Metal-Organic Frameworks for Photochemical Reactionsmolecules in the equatorial sites [31]. A few guest bpe molecules were also found in the lattice along with lattice water.…”
Section: Polymerization Of a Hydrogen-bonded Metalmentioning
confidence: 98%
“…As with the other examples, optical microscopy revealed that the transparency and shape of the crystals along with their singlecrystal nature were retained during the photoreaction, which suggested that the reaction occurred via an SCSC transformation. Final example of metalion -induced photodimerization is the coordination complex [Zn(bpe) 2 109 Interestingly, even this coordination complex forms parallel and crisscross double bonds, which undergoes photochemical [2 + 2] cycloaddition in the solid state and produces rctt -tetrakis(4 -pyridyl)cyclobutane in up to 100% yield of photodimers with rctt -tpcb as major and rtct -tpcb as minor…”
mentioning
confidence: 99%